The factory móveis cimo and their furniture: Is school an attractive market A fábrica móveis cimo e seus mobiliários: A escola como um mercado atraente - De Sousa G.R.* (2016)
This research, linked to the discussions about school material culture, aims to understand the relationships between Móveis Cimo Factory and the school market. Therefore, these searches are focused in the relations between the public elementary schools, industry and the State. The selection of these specific categories is based on the understanding that the mass schooling is a phenomenon in the Western world, which is linked to the industrial expansion. It can be understood the circulation of pedagogical ideas spread a knowledge that changed the idealization of school artifacts from a reference standard, internationally accepted and the Móveis Cimo Factory sought to adapt its furniture's to an ideal school model, which contributed to the commercialization of their products.